Review of Polymer‐Based Nanodielectric Exploration and Film Scale‐Up for Advanced Capacitors. (15th April 2019) - Tan, Daniel Q.
Abstract: The uprising demands for electrical power and electrification requires advanced dielectric functionalities including high capacitance density, high energy density, high current handling capability, high voltage, high temperature, high thermal conductivity, light weight, and environmental reliability. Nanodielectric engineering emerges and attracts extensive efforts from many countries as a result. Unlike prior reviews focusing on lab scale nanocomposite study, this review focuses on recent innovations in polymer‐based nanodielectric design on a large scale and their film scale‐up efforts for advanced capacitors. The unconventional polymer‐nanofiller engineering and their process in the last two decades are discussed. The nanofunctionalized polymers on a molecular level for high dielectric constants and high dielectric strength are briefly described. The challenge associated with film scale‐up and retention of nanodielectric properties are then pointed out to be crucial toward a transfer of dielectric and capacitor technology. Several important attempts at scaling up dielectric films and capacitors recently supported by the US government and industry are reviewed. An alternative strategic approach to achieving high performance polymer films is introduced by leveraging 2D surface coating on commercially mature large‐scale polymer films. Future pathways for high quality scalable dielectric films exhibiting desirable dielectric properties and feasibility for capacitor manufacturing are suggested. Abstract : The extensive exploration efforts towards electrically insulating dielectric materials and their structure–process relationship are reviewed. Several polymers and nanodielectric composites have impressed technologists over the past 15 years. Challenges in their conversion to film scale‐up and capacitors are tangible. Some high temperature dielectric film processes show good feasibility of dielectric film scale‐up.